Assessing Phenylalanine Blood Level in Children With Phenylketonuria in Southern Khorasan Province and Determining the Affecting Social and Demographic Factors - Tayebeh Chahkandi; Bita Bijari; Niloofar Hamidi Laeen; Sayeh Shaban; Emad Asgari Jafarabadi (Mazandaran University of Medical Sciences, 2022)
Background: Phenylketonuria is a metabolic disorder resulting from a defect in phenylalanine metabolism with a global prevalence of 1 in 10000. Delayed initiation of dietary modification leads to brain injury and cognitive and behavioral problems. The main objective of this study was to assess the demographic and social factors affecting the metabolic control of patients having phenylketonuria in Southern Khorasan Province, Iran.  Methods: In this cross-sectional descriptive-analytic study which was performed during the summer of 2019, a total of 32 out of 37 known children and adolescents having phenylketonuria in Southern Khorasan Province were assessed. The age and gender of patients, parents' marital status, parents' occupational status, parents' educational level, the distance between home and phenylketonuria clinic, and the number of affected siblings having phenylketonuria were documented. We were not able to contact five patients having phenylketonuria in Southern Khorasan Province. Data were analyzed by SPSS 16 software using the Mann-Whitney U test and the Kruskal-Wallis test. The significance level was considered P<0.05. Results: Totally, 32 patients with a Mean±SD age of 6.6±4.7 years enrolled in this study among whom 23 were male (71.9%) and 9 patients were female (28.1%). The Mean±SD phenylalanine level in this study group was 8.1±5.2 mg/dL. The disease was optimally controlled in 14 patients (43.3%) and poorly controlled in 18 patients (56.3%). There was not any statistically significant relation between the metabolic control of the disease and any of the assessed social and demographic factors. Conclusions: The disease was properly controlled in 43.3% of the assessed population, and 56.3% had poor metabolic control. There was not any statistically significant relation between the metabolic control of patients having phenylketonuria in Southern Khorasan Province and the assessed demographic and social variables. As the number of known cases in South Khorasan province is limited, the small sample size could be one of the main limitations of our study.